2016
DOI: 10.1161/circinterventions.116.004058
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Shear-Thinning Hydrogels for Minimally Invasive Delivery to Infarcted Myocardium to Limit Left Ventricular Remodeling

Abstract: Background Injectable, acellular biomaterials hold promise to limit left ventricular (LV) remodeling and heart failure precipitated by infarction through bulking and/or stiffening the infarct region. A material with tunable properties (e.g., mechanics, degradation) that can be delivered percutaneously has not yet been demonstrated. Catheter deliverable soft hydrogels with in vivo stiffening to enhance therapeutic efficacy achieve these requirements. Methods and Results We developed a hyaluronic acid hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(134 citation statements)
references
References 41 publications
3
131
0
Order By: Relevance
“…Here, hydrogels are used for mechanical bulking, 3,4,35 modulating remodeling, 7,17 or therapeutic delivery (cells, small molecules, RNAs) after infarction. 6,15,45 An additional advantage of injectable hydrogels in cardiac disease is the potential to deliver material through minimally invasive approaches, such as percutaneously through a catheter.…”
Section: Methods 3: Injection Of Hydrogels Into Cardiac Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, hydrogels are used for mechanical bulking, 3,4,35 modulating remodeling, 7,17 or therapeutic delivery (cells, small molecules, RNAs) after infarction. 6,15,45 An additional advantage of injectable hydrogels in cardiac disease is the potential to deliver material through minimally invasive approaches, such as percutaneously through a catheter.…”
Section: Methods 3: Injection Of Hydrogels Into Cardiac Tissuesmentioning
confidence: 99%
“…34,35 For tissue regeneration, the encapsulation of cells within hydrogels also requires specific injection parameters that can influence viability. 6,36 For bioprinting applications, injection parameters are also important in modulating both the resolution and stability of printed structures, as well as cellular viability.…”
Section: Introductionmentioning
confidence: 99%
“…The size and shape of the hydrogel injections (Figure 1, Table 1) were based on MRI reconstruction of injected explant tissue from a previous study. For more detail related to that experimental data, please see the Supplemental Material section in (Rodell et al, 2016). The geometry of the LV wall was based on experimental measurements from ovine hearts (Rodell et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Several formulations of injectable biomaterials have been studied in order to evaluate the impact on wall thickness and global LV function (Dorsey et al, 2015; Ifkovits et al, 2010; Morita et al, 2011; Tous et al, 2011). These in vivo studies have demonstrated that injectable hydrogel injections can mitigate the adverse effects of MI (Dorsey et al, 2015; Rodell et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation